INOVATION AND MANIFESTATION (EXISTENCE): THE SUBJECT-MATTERS OF LEGAL PROTECTION OF INTELLECTUAL PROPERTY CONCEPTUALIZING INTELLECTUAL PROPERTY IN THE CONTEXT OF LEGAL PROTECTION THE CONCEPT OF INTELLECTUAL PROPERTY AS A SUBJECTOF LEGAL PROTECTION - Dr. Jehad Saleh Qwaider Baniyniss (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The concept ofLegal Protection of intellectual property in the context of this paperis to find the means of preservingitsexistence and to prevent its abuse, whether the matter is related to the owner or the author of the work,regarding thepersonal qualities such asthe productive imagination, orinnovative idea or intellect that may actually be put into existence in the form a book or lecture, or theater arts or drawing or painting works, or through the creationof a futuristic image full of wide range of perceptions and expressions dissimilarto theprevailing one.That kind of a talented individual is protected by the law in appreciation of his efforts and productive epitomes. The law, in addition to that, ambiences him with a protectoral fence that preserves what he has been able to produce for either the benefit of the present or future generations of his country. This, in no doubt, will encourage others who may be possessing similar ideas to trailsuch an example. Therefore, the law streamlinesan adequate protective regulations for these kinds of innovative ideas through the means of a Legal protection, as the possession of innovative idea may not be enough alone without it being protected by the law. Therefore, in addition to that, and if necessary,thesenoble ideas of innovation and creation should be made to be visible, exist andperceptiblephysically,regardless of its type or method or expression or importance or purpose.